ANALISIS KESULITAN MAHASISWA DALAM MENYELESAIKAN SOAL KALKULUS BERDASARKAN TAHAPAN PEMECAHAN MASALAH POLYA - Novita Erni Hendrawati; Teguh Santoso; Mokh. Dedi Penta Putra (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aimed to analyze students’ difficulties in solving calculus problems based on Polya’s problem-solving stages. The study employed a qualitative approach with a descriptive research design. The participants consisted of 18 students of the Mathematics Education Study Program who had completed the Calculus course. Data were collected through written tests and interviews. Furthermore, three subjects were purposively selected for in-depth analysis based on variations in ability and characteristics of their responses. Data analysis was conducted using Polya’s problem-solving stages, namely understanding the problem, devising a plan, carrying out the plan, and looking back. The findings revealed that students experienced difficulties across all stages of problem solving with varying levels of occurrence. At the understanding stage, students encountered difficulties in identifying the concept of definite integrals. At the planning stage, students tended to apply procedures mechanically. The most dominant difficulties occurred in carrying out the plan and looking back, as indicated by errors in applying concepts, algebraic operations, and limited evaluation of the obtained solutions.